Bond behavior between basalt fibres reinforced polymer sheets and steel fibres reinforced concrete - Yuan, C.; Chen, Wensu; Pham, Thong; Hao, Hong (Pergamon, 2018)
Bonding behavior between FRP and Steel fibre reinforced concrete is not well studied. This study experimentally investigates the interfacial bond behavior between basalt fibre reinforced polymer sheet (BFRP) and steel fibre reinforced concrete (SFRC). Short steel fibres with four volume fractions were used to investigate the interfacial bond behavior of BFRP-SFRC as the mechanical properties of the concrete substrate (i.e. compressive strength and tensile strength) can be improved by adding steel fibres. The effects of volume fraction on the bond strength, effective bond length, local slip at the peak shear stress, and interfacial bond-slip relationship are evaluated and discussed. The experimental results showed that the debonding process becomes more ductile as the debonding plateau in the load and displacement curves has been significantly extended. Findings from the present tests show that the specimens with steel fibres of 0.25%, 0.50% and 1.0% experienced significant increase in the peak interfacial shear stress up to 31%, 53%, and 76% over the control specimen without steel fibres, respectively. In addition, the analytical bond strength models and interfacial bond-slip models, incorporating the effect of short steel fibres, are proposed.